The hunt after Jeanne-Antoinette de Pompadour : patronage, politics, art, and the French Enlightenment - Hooper-Hamersley, Rosamond, 1952- (Lexington Books, 2011)
This book recast the import of Mme de Pompadour as a political and artistic patron at the cour of Versailles in mid eighteenth century France. Her visual record is lush and archival and printed sources demonstrate the degree to which she dazzled and enlightened culture, leaver her considerable imprint on pre-revolutionary France.